Distribution, Population Dynamics, and Characteristics of Ice Nucleation-Active Bacteria in Deciduous Fruit Tree Orchards - Gross, Dennis C. (1983)
Deciduous fruit tree orchards located in the Pacific Northwest were surveyed over a 3-year period for the presence of ice nucleation-active (INA) bacteria. In the Yakima Valley, only about 30% of the fruit tree orchards contained INA bacteria (median population ca. 3 × 10(2) CFU/g [fresh weight]) in contrast to nearly 75% of the orchards in the Hood River Valley (median population ca. 5 × 10(3) CFU/g [fresh weight]). These INA populations ranged from less than 10 to over 10(6) CFU/g (fresh weight) of blossoms and, in Hood River Valley orchards, generally comprised over 10% of the total bacterial population. Populations of INA bacteria fluctuated during the year with highest levels developing on buds and flowers during the cool, wet spring, followed by a drop in populations during the warmer, drier, summer months and finally a gradual increase in the autumn. The INA bacteria persisted on dormant buds from which they again colonized young developing vegetative tissues. All INA bacteria were identified as Pseudomonas syringae. The frequency of ice nucleation at −5°C for these strains ranged from nearly every cell being INA to less than 1 in 10(7) cells. The median frequency of ice nucleation at −5°C was 10(4) cells per ice nucleus. The INA P. syringae strains from individual orchards were diverse with respect to bacteriocin typing and in ice nucleation frequency. The consistent absence of detectable INA bacteria or presence of low populations in most of the orchards surveyed during periods when critical temperatures (i.e., −2 to −5°C) were common indicated a limited role for INA bacteria in frost susceptibility of most Pacific Northwest orchards.